Pengaruh Laverage, Profitabilitas, Ukuran Perusahaan Dan Tingkat Inflasi Terhadap Pertumbuhan Laba - Tien Kartika Kumala Dewi; Kartika Hendra Titisari; Purnama Siddi (Owner : Riset dan Jurnal Akuntansi, 2022)
The objective of this study was to determine whether there is an effect or influence between leverage as an indicator of Debt to Equity Ratio (DER) variable, profitability as an indicator of Return On Equity (ROE) variable, company size estimatet by total assets and inflation rate on profit growth. in companies operating in the consumer goods industry sector and listed on the 2017-2019 list of the Indonesia Stock Exchange. With a sample of 40 companies from the entire population used in this study, there are 52 companies are active in the consumer goods industry sector and have been listed on the Indonesia Stock Exchange for the period 2017-2019. Then the approach used in this study is a quantitative approach with multiple linear regression analysis techniques that can show that a part of the leverage variable affects earnings growth with a significance value of 0.000 <0.05. The profitability variable has an effect on profit growth with a significance value of 0.000 <0.05. The inflation rate variable has an effect on profit growth with a significance value of 0.044 <0.05. While the size of the company has no effect on profit growth because the significance value is 0.132 > 0.05. Simultaneously, the variables of leverage, profitability, firm size and inflation rate affect profit growth with a significance-values-of 0.000 <0.05.